PRINCIPLES, FORMS, AND METHODS OF MEDIA-LEARNING IN TEACHING COMPUTER SCIENCE (Uzbekistan Open Conference, 2026)
The role of modern forms and methods, scientific and theoretical oundations, and factors for their effective application in teaching computer science are the development of an integrated system.